Expert Reception of The Limits to Growth: A Few Simple Tools for the Book Historian - Knott, Cheryl (Knygotyra, 2022)
In the early 1970s, a research team at the Massachusetts Institute of Technology used new methods of computer modelling to simulate global dynamic processes. The outcome of their work was a series of projections of the depletion of natural resources worldwide, with potentially dire consequences for the environment and the economy. Their report on their modelling and its projections was issued as a book in 1972, entitled The Limits to Growth. It created an immediate debate among scholars, policy makers, and other educated readers, and publications citing The Limits to Growth over its lifespan are voluminous. It continues to be cited 50 years after it was issued. The long citation period and the varied responses over time pose challenges for the book historian seeking to characterise the reception of the book. This article explores the ways in which book historians can use readily available citation analysis and visualisation tools to deepen understanding of a book’s reception beyond the qualitative methods typically used in the secondary literature. The Web of Science’s citation indexing and the HathiTrust collection’s full-text searching capability are used to identify articles and books that have cited or referred to The Limits to Growth. Examples of the visualisations generated from the search results in each are included as illustrations of simple, accessible tools that the lone book historian can use when the scale of his or her work does not require the kind of computational analytics created to parse big textual data in digital humanities projects.
Keywords: Citation analysis; The Limits to Growth; reception; Web of Science; environmental studies